Multitarget Direct‐Acting Antiviral Therapy Is Associated With Superior Immunologic Recovery in Patients Coinfected With Human Immunodeficiency Virus and Hepatitis C Virus. Issue 12 (27th September 2018) - Shrivastava, Shikha; Bhatta, Manasa; Ward, Haley; Romani, Sara; Lee, Rebecca; Rosenthal, Elana; Osinusi, Anu; Kohli, Anita; Masur, Henry; Kottilil, Shyam; Wilson, Eleanor
Abstract : Patients coinfected with human immunodeficiency virus (HIV) and hepatitis C virus (HCV) have higher levels of immune activation, impaired antigen‐specific responses, and accelerated fibrogenesis compared to patients monoinfected with HCV. Whether different direct‐acting antiviral (DAA) combinations have differential effects on immunophenotypes and functions following successful HCV therapy remain unknown. Therefore, we aimed to assess the peripheral T‐cell immunophenotypes and functions in patients coinfected with HIV/HCV who were successfully treated with combination DAA treatment regimens. We analyzed peripheral blood mononuclear cells (PBMCs) at baseline and at the time of sustained viral response (SVR) from subjects treated with three different combination DAA regimens: daclatasvir (DCV) and asunaprevir (ASV) for 24 weeks (CONQUER 2‐DAA), DCV/ASV/beclabuvir (BCV) for 12 weeks (CONQUER 3‐DAA), and sofosbuvir (SOF) and ledipasvir (LDV) for 12 weeks (ERADICATE study). We used flow cytometry to assess T‐cell phenotypes (activation and exhaustion) and HCV‐specific T‐cell functions (cytokine secretion and cytotoxicity). Statistical analyses were conducted using the Wilcoxon matched‐pairs signed‐rank test with P < 0.05 considered significant. Overall, there was an improvement in T‐cell exhaustion markers, a decrease in T‐cell activation, an increase in the effector memory population, and improved T‐cell function after achieving SVR, with the largest effects noted with CONQUER 3‐DAA treatment. Conclusion: Treatment with DCV/ASV/BCV in patients coinfected with HIV/HCV resulted in greater restoration of the T‐cell impairments and perturbations associated with HIV/HCV coinfection to an extent that was greater than that observed in either two‐drug regimens. We showed that different DAA‐based therapies have different immunologic outcomes after successful HCV treatment in patients coinfected with HIV/HCV. This information will be beneficial for providers when selecting the regimens for patients coinfected with HIV/HCV. Abstract : Triple DAA‐based therapy, targeting three steps in the HCV replication cycle have a profound effect in restoration of the T‐cell impairments and perturbations such as reducing immune activation, exhaustion and restoring immune function in HIV/HCV co‐infected patients.